MSP430-based Robot Applications : A Guide to Developing Embedded Systems - Harres, Dan, author 549626 (Oxford : Newnes, 2013)
This book provides a careful explanation of the basic areas of electronics and computer architecture, along with lots of examples, to demonstrate the interface, sensor design, programming and microcontroller peripheral setup necessary for embedded systems development. With no need for mechanical knowledge of robots, the book starts by demonstrating how to modify a simple radio-controlled car to create a basic robot. The fundamental electronics of the MSP430 are described, along with programming details in both C and assembly language, and full explanations of ports, timing, and data acquisition. Further chapters cover inexpensive ways to perform circuit simulation and prototyping.